FACTORS AFFECTING ADOPTION OF PADDY ESTATE PROJECT AMONG RICE FARMERS FOR INCREASING RICE PRODUCTION AND SUPPLY - Ali, Jamal; Othman, Zakirah; Zaman, Nur Badriyah Kamarul (International Journal of Supply Chain Management, 2019)
Abstractâ?? Rice is an important commodity in Malaysia as it is the most prominent staple food of the population. The National Agrofood Policy of Malaysia highlighted the need to ensure adequate rice supply and to increase farmersâ?? income level. One of the efforts to increase rice production is the implementation of the Paddy Estate Project (PEP). The objective of the programme is to increase rice production with a lower operating cost. The present paper provides a case study of rice farmers in the Muda granary area, which covers the states of Kedah and Perlis, using primary data to identify the factors on the adoption of PEP among farmers. The research findings indicate that the key factors determining the farmersâ?? adoption of the PEP are age, secondary jobs, effective communication with the extension agency, increased rice yield, lower operating cost, lower working time in the fields, and support services, such as assistance, incentives, and facilities from the government.